The incidence of using problem-based learning (PBL) strategy on the level of listening skill development for students attending the third year of bachillerato at Unidad Educativa Jorge Rodríguez Román located in canton of Orellana during the first quimester of 2015-2016 school year - Carpio Celi, Rosenda Alba (2016)
This research mainly aims to demonstrate the incidence of use of the Problem Based- Learning strategy to improve the performance of the listening skill for students attending the third year of Bachillerato at Unidad Educativa Jorge Rodríguez Román located in canton Fco. Orellana, in the Province of Orellana. The teaching of English is inefficient in schools of public education due to many factors such as logistical and pedagogical problems, which is reflected in the listening skill learning. This research presents the Problem Based- Learning strategy as a solution to this problem which main objective is to increase the cognitive part of students by using specific steps. The teacher has the role of facilitator and moderator, and students are the center of the process because while they are working in groups or individually they are seeking an answer to a problem posed by unresolved. A control and an experimental group were needed for the application of the methodology design. Both experimental and control group took an initial and final exam. The results of those tests were analyzed and processed statistically to reach the conclusion that the use of the Problem Based- Learning strategy did have a positive effect on the students of the experimental group. At the end of this research, a proposal as an alternative based on the use of the Problem-Based Learning strategy is presented in order to improve the listening skill on students of English.